Rock Aggregate Potential of Limestone Units in the Khyber Formation, Pakistan - Muhammad Naveed Anjum; Nowrad Ali; Zaif Ur Rehman; Muhammad Ghayas; Waqas Ahmad (International Journal of Economic and Environmental Geology, 2018)
The Precambrian carbonates of the Khyber Formation are evaluated in terms of their petrographic, geochemical and physico-mechanical properties for assessing their suitability as an aggregate source both in asphalt and concrete works. The Khyber Formation is extensively exposed in the eastern and central parts of the district Khyber, Khyber Pakhtunkhwa. The limestone units of the Khyber Formation dominantly comprise calcite (CaCO3 ;94 98%) with minor to trace concentration of dolomite, undeformed quartz and ores. The limestone of the Khyber Formation is classified as Algal laminated micritic mudstone. It is light to dark-grey, hard, compact, and thin to medium bedded and at places thick-bedded. The algal stromatolites and laminations are common. The stylolites, calcite-filled veins and neomorphism are the common diagenetic modifications in these carbonates. The limestone of the Khyber Formation is composed of 54.72-58.4 wt. % CaO3, 0.5-0.9 wt. % MgO and based on a 0.02-0.22 wt. % combined values of K2O and Na2O, and it is classified as low to high alkali limestone. Massive outcrops of dolomitized-limestone have also been identified sporadically along the exposed outcrops of the Khyber Formation e.g. in Besai area and along Khyber Pass. The petrographic and chemical investigations show that the limestone units of the Khyber Formation are innocuous in terms of Alkali Silica Reactivity (ASR) and Alkali Carbonate Reactivity (ACR). However, the dolomitized horizons must be avoided, owing to its ACR potential while selecting a quarry site for aggregate extraction. The physical properties of the limestone units of the Khyber Formation as an aggregate material (i.e. soundness, water absorption, Los Angles abrasion, specific gravity and unconfined compressive strength) are in accordance with the ASTM standards. The petrographic, geochemical and geotechnical details of the limestone units in Khyber Formation approve their suitability as an aggregate source in both concrete and asphalt construction works.